Factors associated with tocolytic hospitalizations in Taiwan: evidence from a population-based and longitudinal study from 1997 to 2004 - Tsai Eing-Mei; Norton Edward C; Ma Ke-Zong; Lee Shoou-Yih (BMC, 2009)
Abstract Background The use of tocolytic hospitalization in antenatal care is controversial and worthy of more research. We investigated individual, institutional, and area factors that affect the use of tocolytic hospitalizations in Taiwan where fertility has rapidly declined. Methods Longitudinal data from the 1996 to 2004 National Health Insurance Research Database in Taiwan were used to identify tocolytic hospitalizations. The probit model was used to estimate factors associated with tocolytic hospitalizations. Results The decline in fertility was significantly associated with the probability of tocolytic hospitalizations. Several physician and institutional factors-including physician's age, hospital ownership, accreditation status, bed size, and teaching status-were also significantly correlated to the dependent variables. Conclusions The provision of inpatient tocolysis is influenced not only by clinical considerations but also by physician, institutional, and area factors unrelated to clinical need. Fertility declines in Taiwan may have led obstetricians/gynecologists to provide more tocolysis to make up for their lost income. If the explanation is further validated, reimbursement policies may need to be reviewed to correct for overuse of inpatient tocolysis. The correlation could also be explained by the increasing use of artificial reproductive technologies and higher social value of newborns. In addition, the physician and institutional variations observed in the study indicate potential misuse of inpatient tocolysis that warrant further investigation.